Nascita di un nome. Esercizi di memoria sul patrimonio immateriale della dieta mediterranea - Elisabetta Moro (Archivio Antropologico Mediterraneo)
The author reconstructs the genealogy of the term “Mediterranean diet” and its introduction into the scientific lexicon and in the western general sense. Indeed, this expression dates back only to the second half of the twentieth century. After collecting witnesses and analyzing the sources, Moro points out that Ancel Keys and Margaret Haney Keys, the discoverers of this way of life, invented this successful expression. They showed the health benefits of the Mediterranean Diet through the Seven Countries Study (1958). Thanks to the book How to Eat Well and Stay Well. The Mediterranean Way (USA 1975) the Keys introduced the expression “Mediterranean diet” into the western lexicon. However, this term officially enters into the scientific lexicon thanks to research carried out on the relationship between diet and cholesterol. The study was strongly desired by Ancel Keys and performed by Anna Ferro-Luzzi et all. in Cilento-Italy (today one of the UNESCO communities of the Mediterranean diet). This research was published in 1984 in the prestigious American Journal of Clinical Nutrition AJCN.